2014
DOI: 10.1111/jdv.12516
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue and coronary artery calcification in psoriasis patients

Abstract: This study showed that psoriasis was associated with increased EAT volume independently of visceral abdominal fat and with subclinical atherosclerosis. Within psoriasis patients EAT volume was independently associated with CAC. EAT may be another important contributor to the higher cardiovascular risk observed in psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 46 publications
1
39
1
Order By: Relevance
“…Indeed, a recent hospital‐based survey revealed that psoriasis vulgaris is associated with the incidence of coronary heart diseases in Japanese . Our observation is also consistent with previous reports that the relative risks of CVD in severe psoriatic patients are greatest in younger individuals …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Indeed, a recent hospital‐based survey revealed that psoriasis vulgaris is associated with the incidence of coronary heart diseases in Japanese . Our observation is also consistent with previous reports that the relative risks of CVD in severe psoriatic patients are greatest in younger individuals …”
Section: Discussionsupporting
confidence: 92%
“…Epicardial adipose tissue functions as a paracrine organ by releasing bioactive adipocytokines into the adjacent interstitium of the myocardium and coronary arteries, and may represent cardiovascular risk . Recent studies have shown significantly higher EAT volume in psoriatic patients compared with control subjects, and EAT was independently associated with the presence of CAC . There is a correlation between EAT and BMI or metabolic syndrome, but Japanese psoriatic patients comprise only 0.34% of the population, with metabolic syndrome and obesity generally much less prevalent than Caucasians .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased epicardial adipose tissue (EAT) has been associated with autoimmune disorders, such as psoriasis (5) and rheumatoid arthritis (6), and with cardiometabolic diseases such as type 2 diabetes mellitus (7), coronary artery disease (CAD) (811), and atrial fibrillation (12,13). It is postulated that close proximity of the increased EAT to the heart and vessels (14) and the lack of a physical barrier between these structures allow for diffusion of proinflammatory cytokines that could play role in the development of cardiometabolic diseases (14–16).…”
Section: Introductionmentioning
confidence: 99%